High Specific Capacity Thermal Battery Cathodes LiCu2O2 and LiCu3O3 Prepared by a Simple Solid Phase Sintering - Wang, Yan; Bai, Xintao; Luo, Zeshunji; Fu, Licai (Frontiers in Chemistry, 2020)
The long storage life, large capacity and long working time make the thermal battery apply to the storage and emergency power. The thermal battery has been designed to active at high temperature to satisfy the storage and large capacity. As the development of thermal battery with high specific energy and long working time requires that the cathode has high thermal stability and excellent conductivity. Here, the semiconductor material Li-Cu-O compounds LiCu2O2 and LiCu3O3 are synthesized by a simple solid phase sintering technique. The thermal decomposition temperatures are 680℃ and above 900℃, respectively. With a cut-off voltage of 1.5V, the specific capacities of LiCu2O2 and LiCu3O3 are 423 mAh g-1 and 332 mAh g-1. Both the decomposition temperature and specific capacity are higher than the commercial FeS2 and CoS2, especially LiCu2O2. This work first applies the Li-Cu-O compounds to the thermal battery, and affords an alternative of the cathode materials for high specific capacity thermal battery.